Computational Approach to Identifying New Chemical Entities as Elastase Inhibitors with Potential Antiaging Effects - Pitasi, Giovanna; Brancale, Andrea; Floris, Sonia; Fais, Antonella; Gitto, Rosaria; De Luca, Laura (International journal of molecular sciences, 2024)
In the aging process, skin morphology might be affected by wrinkle formation due to the loss of elasticity and resilience of connective tissues linked to the cleavage of elastin by the enzymatic activity of elastase. Little information is available about the structural requirements to efficiently inhibit elastase 1 (EC 3.4.21.36) expressed in skin keratinocytes. In this study, a structure-based approach led to the identification to the pharmacophoric hypotheses that described the main structural requirements for binding to porcine pancreatic elastase as a valuable tool for the development of skin therapeutic agents due to its similarity with human elastase 1. The obtained models were subsequently refined through the application of computational alanine-scanning mutagenesis to evaluate the effect of single residues on the binding affinity and protein stability; in turn, molecular dynamic simulations were carried out; these procedures led to a simplified model bearing few essential features, enabling a reliable collection of chemical features for their interactions with elastase. Then, a virtual screening campaign on the in-house library of synthetic compounds led to the identification of a nonpeptide-based inhibitor (IC50 = 60.4 μM) belonging to the class of N-substituted-1H-benzimidazol-2-yl]thio]acetamides, which might be further exploited to obtain more efficient ligands of elastase for therapeutic applications.
Keywords: pankreatická elastasa; Structure-Activity Relationship; prasata; vztahy mezi strukturou a aktivitou; Swine; simulace molekulového dockingu; Pancreatic Elastase; Molecular Dynamics Simulation; simulace molekulární dynamiky; Animals; lidé; Molecular Docking Simulation; Humans; zvířata